COVID-19 Pandemic, Economic Loses and Education Sector Management - Sampson Atuahene; Yusheng Kong; Geoffrey Bentum-Micah (Yayasan Ahmar Cendekia Indonesia, 2020)
The outbreak of the new coronavirus (COVID) started in December 2020. By far, the COVID-19 has affected over 26,547,419 individuals worldwide, with 874,424 deaths and 18,732,160 recoveries as of August 2020. The research aims at identifying the effects of COVID-19 on education sector management pointing out success stories of countries that have been able to overcome the hindrances that the pandemics have brought on the management of the various sectors of education, which other countries may adopt. From our analysis, we discovered that combating COVID-19; demands syndrome surveillance, immediate isolation of patients, and strict enforcement of all contact-persons, quarantine, and country lockdown/border closure. We further outlined ways in which COVID-19 (coronavirus) epidemics affect the education of emerging economies. Our article then summarizes the evidence of a negative impact that is likely to disrupt the education system and identifies some policy responses to mitigate the effects. We again realized that what could save education (school system) now and in the future is online learning which authorities should make available, accessible, and affordable especially for developing countries.